The First Magnetotelluric Image of the Lithospheric-Scale Geological Architecture in Central Svalbard, Arctic Norway - Beka, Thomas Ibsa; Smirnov, Maxim; Bergh, Steffen G; Birkelund, Yngve (Polar Research, 2015)
Magnetotelluric data, collected from 30 stations on Spitsbergen as part of a reconnaissance geothermal resource assessment along a profile with 0.53-km spacing in 0.0031000-s period range, were used to develop a lithospheric-scale two-dimensional (2D) resistivity model, heretofore unavailable for the region. Inverting the determinant of the impedance tensor in 2D, we found the smoothest model fitting the data within a specified tolerance level. We justified the model by perturbing it, performing sensitivity analysis and re-running the inversion with a different algorithm and starting models. From our final model, we constructed a crustal-scale stratigraphic framework, using it to estimate the depth of major geological features and to locate structural deformations. The 2D resistivity model indicates a shallow low resistive (B100 Vm) Paleozoic Mesozoic sedimentary sequence, varying laterally in thickness (24 km), obstructed by a gently dipping PermianCarboniferous succession (1000 Vm) east of the Billefjorden Fault Zone. Underneath, a (possibly Devonian) basin is imaged as a thick conductive anomaly stretching 15 km downwards. Beneath a deformed PaleozoicMesozoic successions, an uplifted pre-Devonian shallow basement (3000 Vm) is revealed. We estimated a thin lithosphere, in the range of ca. 55100 km thick, that could explain the area’s elevated surface heat flow (ca. 6090 mW/m2 ), consistent with the calculated depth of thermal lithosphere heat-base boundaries for a partially melting mantle. The model indicates a possible replenishment pathway of upward heat transport from the shallow convective mantle to the composite crustal conductive units. This is encouraging for low-enthalpy geothermal development. Human set